PENGARUH PEMASARAN INTERNAL TERHADAP ORIENTASI PASAR (STUDI PADA BANK PERSERO DI DENPASAR) - Jaya, Iwan Trisna; Wardana, I Made; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.12.TAHUN 2014, 2015)
The study aims to look at the effect of internal marketing on market orientation through organizational commitment and OCB at state-owned banks (Mandiri, BNI, BRI) in Denpasar. All employees of state-owned banks in Denpasar is the study population. The number of samples in this study set 179 respondents. Convenience sampling selected as the sampling method of front liner employees (tellers and customer service), marketing and branch leaders. The data is processed and analyzed by SEM through AMOS software. The results showed that: (1) The relationship between internal marketing on market orientation, internal marketing on organizational commitment, internal marketing on OCB, is positive and significant. (2) The effect of organizational commitment on market orientation, organizational commitment on OCB, is positive and significant. (3) OCB has a positive and significant impact on market orientation. (4) organizational commitment and OCB is a mediating variable between internal marketing and market orientation. (5) Organizational commitment as a mediating variable between internal marketing and OCB. (6) OCB is a mediating variable between organizational commitment and market orientation. Keywords : Internal Marketing, Organizational Commitment, Organizational Citizenship Behaviour (OCB), Market Orientation.
Keywords: Internal Marketing, Organizational Commitment,Organizational Citizenship Behaviour (OCB), Market Orientation.